THE RELATIONSHIP OF NURSE CHARACTERISTICS TO UNDERSTANDING COMPLETENESS OF DOCUMENTATION IN CLIENTS WITH ENDOCRINE DISORDERS AT RS "X" 20223 - Wiratikusuma, Yohana; Rahayu, Previarsi (Jurnal Ilmiah Keperawatan, 2024)
Background: The care of clients with endocrine disorders is often characterized as continuous and complex. Lack of understanding of the completeness of nurse documentation as an evaluation of nurses' compliance with low quality nursing practice standards can result in misdiagnosis and inappropriate treatment for clients. Objective: To determine the relationship between nurses' characteristics (age, gender, education) regarding their knowledge and understanding of the documentation of nursing care for clients with endocrine disorders as an evaluation of nurses' compliance with practice standards. Methods: Quantitative descriptive correlation cross sectional design, conducted February - August 2023 in two hospitals in West Java. A total of 112 nurses using the Simple Random Sampling technique became respondents. Data analysis of data using multiple logistic regression. Results: It is known that there is a significant relationship between age and knowledge of understanding related to nursing care (p value = 0.039), There is a significant relationship between education and knowledge of understanding related to nursing care (p value = 0.000). There is a significant relationship between gender and knowledge (p value = 0.00). Conclusion: There is a relationship between age, education level and gender on understanding related to nursing care evaluation of compliance with nursing practice standards in X Hospital in 2023.